2018
DOI: 10.1080/10717544.2018.1461958
|View full text |Cite
|
Sign up to set email alerts
|

Cefquinome-loaded microsphere formulations againstKlebsiella pneumoniainfection during experimental infections

Abstract: The aim of this study was to prepare cefquinome-loaded polylactic acid microspheres and to evaluate their in vitro and in vivo characteristics and pharmacodynamics for the therapy of pneumonia in a rat model. Microspheres were prepared using a 0.7 mm two-fluid nozzle spray drier in one step resulting in spherical and smooth microspheres of uniform size (9.8 ± 3.6 μm). The encapsulation efficiency and drug loading of cefquinome were 91.6 ± 2.6% and 18.7 ± 1.2%, respectively. In vitro release of cefquinome from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…We carried out research on extracting protocatechuic aldehyde from the aerial part of S. miltiorrhiza, and explored its main medicinal effects. Although the effects of polysaccharides and some TCM monomers on inflammatory factors have been studied, the effects of PAI on inflammatory factors remain unknown [ 20 , 21 ]. In the present study, we found that the administration of PAI improved the survival rate of mice and cells and attenuated the LPS induced acute phase response in an LPS mice model.…”
Section: Discussionmentioning
confidence: 99%
“…We carried out research on extracting protocatechuic aldehyde from the aerial part of S. miltiorrhiza, and explored its main medicinal effects. Although the effects of polysaccharides and some TCM monomers on inflammatory factors have been studied, the effects of PAI on inflammatory factors remain unknown [ 20 , 21 ]. In the present study, we found that the administration of PAI improved the survival rate of mice and cells and attenuated the LPS induced acute phase response in an LPS mice model.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of caspase-9 and -3 activities and TNF-␣ and IL-1␤ levels. The supernatants (stored at -80°C) were used to determine the activities of caspase-3 and caspase-9 (Nanjing Jian Cheng Biotechnology Co., Ltd., Nanjing, China) and TNF-␣ and IL-1␤ (R&D Systems, Minneapolis, MN) using commercial ELISA kits according to manufacturers' instructions (51).…”
Section: Methodsmentioning
confidence: 99%
“…We obtained PLGA microspheres of different particle sizes (3 mm: PLGA-3; 10 mm: PLGA-10; 25 mm: PLGA-25; 40 mm: PLGA-40,) through improving a method described by Qu et al (Fig. S1) [5]. To obtain the optimal particle size for lung-targeting, we performed imaging experiments for lung blood vessels using micro CT (Fig.…”
Section: Effect Of Microspheres Sizes On the Lung-targetingmentioning
confidence: 99%
“…Administration to the lungs through the capillaries for innovative formulation is a promising method [2]. Passive lung-targeting microspheres based on microembolism can directly reach the lungs, allowing localized precision treatment of the respiratory system disease, and greatly improving drug bioavailability [5,6,7]. Studies have proven that biodegradable microspheres have achieved effective pulmonary delivery of drug and treatment of pulmonary diseases in animal models [8,9,10].…”
Section: Introductionmentioning
confidence: 99%